2009
DOI: 10.1021/es901515y
|View full text |Cite
|
Sign up to set email alerts
|

Determining Air Quality and Greenhouse Gas Impacts of Hydrogen Infrastructure and Fuel Cell Vehicles

Abstract: Adoption of hydrogen infrastructure and hydrogen fuel cell vehicles (HFCVs) to replace gasoline internal combustion engine (ICE) vehicles has been proposed as a strategy to reduce criteria pollutant and greenhouse gas (GHG) emissions from the transportation sector and transition to fuel independence. However, it is uncertain (1) to what degree the reduction in criteria pollutants will impact urban air quality, and (2) how the reductions in pollutant emissions and concomitant urban air quality impacts compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Replacing the current on-road LDV fleet with FCEVs would reduce net GHG emissions in the U.S [25,26] and CA [27] with similar findings reported for pollutant emissions at various scales [28e30]. In particular, FCEVs supplied with hydrogen produced via renewably powered electrolysis can achieve large-scale reductions in total emissions from transportation [31].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Replacing the current on-road LDV fleet with FCEVs would reduce net GHG emissions in the U.S [25,26] and CA [27] with similar findings reported for pollutant emissions at various scales [28e30]. In particular, FCEVs supplied with hydrogen produced via renewably powered electrolysis can achieve large-scale reductions in total emissions from transportation [31].…”
Section: Introductionsupporting
confidence: 54%
“…While studies have shown that FCEV driven reductions in direct emissions result in improvements in secondary air pollutants, including ground-level ozone and PM 2.5 [37,38], the body of available literature quantifying impacts on secondary air pollutants is limited. Use of a novel methodology for future hydrogen infrastructure development in the South Coast Air Basin (SoCAB) of CA reported substantial reductions emissions including NO x for the majority of Cases [30] translating to significant AQ improvements (e.g., reductions in peak 8-haveraged ozone and 24-h-averaged PM 2.5 concentrations) [27]. However, existing studies were spatially restricted to select regions of CA (e.g., the SoCAB, Sacramento) or the entire U.S., and assume FCEV penetration is universal throughout the study domain.…”
Section: Introductionmentioning
confidence: 99%
“…To address the need for a comprehensive and fully integrated planning methodology, the Spatially and Temporally Resolved Energy and Environment Tool (STREET) was developed at the University of California, Irvine (UCI) to establish, then quantify and assess the full build-out and roll-out impacts of alternative transportation fuels through a comprehensive and integrated analysis that operates at a high level of spatial and temporal detail [10,11]. In particular, STREET provides the capability to:…”
Section: Introductionmentioning
confidence: 99%
“…Determine infrastructure needs and roll-out strategies for light-duty vehicle hydrogen fueling in a local community [10], and 2. Analyze the long-term environmental impacts (e.g., GHG emissions, air pollutant emissions, and air quality) of fully built-out hydrogen infrastructure scenarios [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation